Die verband tussen 'n geslagshormoonwanverhouding en depressie by vroue - Scholtemeyer, Jacobus Schalk (University of the Free State, 2002)
This study was directed by the following three specific objectives: - Firstly, to present a theoretical synthesis from the literature, which would explain the possible relation between depression and a sex hormone imbalance from a medical hypnoanalytical perspective. - Secondly, to determine whether a statistically significant correlation exists between dysthymia and depression respectively (in terms of two scales of the Millon Clinical Multiaxial Inventory III, namely scales D and CC) and the individual serum values of women's testosterone, progesterone and estradiol (in their oestrogen, progesterone or menopausal phases classified separately or considered jointly). - Thirdly, to determine whether the three relative imbalances of the sex hormones, namely between testosterone and progesterone, between oestrogen and progesterone, and between testosterone and oestrogen, in terms of the Maartens profile (Maartens, 1994), displays a statistically significant correlation with dysthymia and depression in terms of the counts obtained on the scales of the above-mentioned psychometric measuring instrument. Subsequently, it was determined which statistically significant correlation is most significant. In order to achieve these objectives, the following methodology was followed: - Objective 1: A relevant literature survey was conducted. - Objectives 2 and 3: The first 60 women who presented a mild or serious degree of depression in the clinical opinion of Dr. H. Vosloo (a medical practitioner) or the researcher, were selected randomly for the purpose of the research. If they were prepared to participate in the research, they were requested first to complete the information sheet by providing their personal details and then to give written permission that their hormone profile and psychometric data may be used in the research on an anonymous basis. Subsequently they were requested to complete the Beck Depression Inventory (Short Form) and the Millon Clinical Multiaxial Inventory III and to have blood samples taken at specific pathologists. The pathologists then sent their results to Dr. Vosloo, who interpreted it further. At the same time, all the mentioned psychometric measuring instruments were scored and interpreted by the researcher himself and the results of the Maartens profile were obtained from Dr. Vosloo. The results related to each objective, which were obtained in the abovementioned methodological manner, can be summarised as follows for each objective: - Objective 1: It was shown successfully from the literature that nonoverwhelming chronic stress stimulates B-endorphin secretion and testosterone secretion, but as soon as the stressor is conceptualised as overwhelming, it has a testosterone-inhibiting function as a result of the still-rising endorphin levels. It was also demonstrated successfully from the literature, in terms of the medical hypnoanalytical model, that the first time an individual is exposed to the stressor, it is called the Initial Sensitising Event. The second time the individual is exposed to a similar stressor is called the Symptom Producing Event, and the third time it is called the Symptom Intensifying Event. After the third event the stressor is conceptualised as overwhelming in terms of the triple allergenic theory, and the stressor can therefore exert a testosterone-inhibiting function, which explains the presentation of depression in terms of medical hypnoanalysis. - Objective 2: The research results of this objective indicated that there is no statistically significant relation between depression and the individual serum values of the three primary sex hormones. - Objective 3: In the case of this objective, the research results indicated that a relatively low testosterone level (in comparison to the other possible hormone-imbalance classification categories in terms of the Maartens profile) displays the strongest statistically significant relation (p < 0,05) with dysthymia and depression. On the basis of the research results of this investigation, the researcher can therefore conclude that the traditional view of a hormone imbalance (in terms of the deviation of a patient's individual serum values from the mean values) has it's limitations, because this before mentioned hormone imbalance cannot be conceptualised as a cause for depression. A sex hormone imbalance in terms of the Maartens profile can, however, perform such an etiological role.

Hierdie studie is gerig deur die volgende drie spesifieke doelstellings: - Eerstens, om vanuit die literatuur 'n teoretiese sintese aan te bied, wat die moontlike verband tussen depressie en 'n geslagshormoonwanverhouding vanuit 'n mediese hipnoanalitiese perspektief verklaar. - Tweedens, om te bepaal of daar statisties beduidende korrelasies tussen distimie en depressie onderskeidelik (in terme van twee skale van die Milion-kliniese-meervoudige-as-inventaris-III, naamlik skale D en CC) en die individuele serumwaardes van vroue se testosteroon, progesteroon en estradiol (in hul estrogeen-, progesteroon- of menopousale fase afsonderlik geklassifiseer of gesamentlik beskou) is. - Derdens, om te bepaal of die drie relatiewe wanverhoudings van die geslagshormone, naamlik tussen testosteroon en progesteroon, tussen estrogeen en progesteroon, en tussen testosteroon en estrogeen, in terme van die Maartens-profiel (Maartens, 1994), statisties beduidend met distimie en depressie korreleer in terme van die tellings behaal in die skale van die vermelde psigometriese meetinstrument. Daarna is bepaal word watter een van die statisties beduidende korrelasies die beduidendste is. Ten einde aan die doelstellings te beantwoord, is die volgende metodologie gevolg: - Doelstelling 1: 'n Toepaslike literatuurstudie is onderneem. - Doelstelling 2 en 3: Die eerste 60 vroue, wat volgens die kliniese indrukke van dr. H. Vosloo ('n mediese praktisyn) of die navorser, met 'n matige of ernstige graad van depressie gepresenteer het, is vir die doel van die navorsing ewekansig geselekteer. Indien hulle bereid was om aan die navorsing deel te neem, is hulle versoek om eers die inligtingstuk te voltooi deur hulle persoonlike gegewens daarop te verstrek en dan skriftelik toestemming te verleen dat hul hormoonprofiel en psigometriese data anoniem in die navorsing betrek mag word. Daarna is hulle versoek om die Verkorte Beck-depressieskaal en die Millon-kliniese-meervoudigeas- inventaris-III te voltooi en om bloedmonsters by spesifieke patoloë te laat neem. Die patoloë het voorts hul resultate aan dr. Vosloo versend, wat dit verder geïnterpreteer het. Terselfdertyd is al die vermelde psigometriese meetinstrumente deur die navorser self nagesien en geïnterpreteer en is die resultate van die Maartens-profiel van dr. Vosloo verkry. Die resultate ten aansien van elke doelstelling, wat op die bovermelde metodologiese wyse nagevolg is, kan vir elke doelstelling as volg saamgevat word: - Doelstelling 1: Daar is suksesvol uit die literatuur aangedui dat nieoorweldigende langdurige stres, ~-endorfiensekresie en testosteroonsekresie stimuleer, maar sodra die stressor as oorweldigend gekonseptualiseer word, dit as gevolg van die steeds stygende endorfienvlakke 'n testosterooninhiberende funksie het. In terme van die mediese hipnoanalitiese model is daar ook suksesvol uit die literatuur aangedui dat die eerste keer dat 'n individu aan die stressor blootgestel word, dit die inisiële sensitiserende gebeurtenis genoem word. Die tweede keer as hy aan 'n soortgelyke stressor blootgestel word, word dit die simptoomproduserende gebeurtenis genoem en die derde keer die simptoomintensiverende gebeurtenis. Na die derde gebeurtenis word die stressor in terme van die drievoudige allergeenteorie as oorweldigend gekonseptualiseer en kan die stressor dus 'n testosterooninhiberende funksie uitoefen, wat die presentering van depressie in terme van die mediese hipnoanalise verklaar. - Doelstelling 2: Die navorsingsresultate van die doelstelling het getoon dat daar geen statisties beduidende verband tussen depressie en die individuele serumwaardes van die drie primêre geslagshormone is nie. - Doelstelling 3: Die navorsingsresultate van die doelstelling het getoon dat 'n relatiewe lae testosteroonvlak (in vergelyking met die ander moontlike hormoonwanbalans-klassifikasiekategorieë in terme van die Maartens-profiel) die sterkste statisties beduidende verband (p < 0,05) met distimie en depressie het. Die navorser kan dus konkludeer dat die tradisionele siening van 'n hormoonwanbalans (in terme van die afwyking van 'n pasiënt se individuele serumwaardes van die gemiddelde waardes) volgens die navorsingsresultate van die onderhawige ondersoek nie as 'n oorsaak van depressie gekonseptualiseer kan word nie. 'n Geslagshormoonwanverhouding in terme van die Maartens-profiel kan egter wél sodanige etiologiese rol vertolk.
Thesis (Ph.D. (Psychology))--University of the Free State, 2002
Keywords: Depression; Sex hormone-imbalance; Women; Testosterone; Oestrogen; Unconscious; Medical Hypnoanalysis; β-endorphin; Depression, Mental; Affective disorders -- Sex factors; Anxiety -- Endocrine aspects